PENGEMBANGAN MODEL PEMBELAJARAN PEMBENTUKAN PERILAKU DAMAI DENGAN REVITALISASI NILAI KEARIFAN LOKAL NTB DI SEKOLAH DASAR - I Nyoman Suarta; Dwi Istati Rahayu (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: Developing teaching model of peace behavior development through revitalization of local wisdom value NTB at elementary schools. The purpose of this Research and Development was to develop teaching model of peace behavior development through revitalization of local wisdom value NTB at elementary schools.  Subjects of the research were elementary schools students at Nusa Tenggara Barat. Results of the research: (1) modul for teachers, and (2) learning materials for students. The modul are emphasized in developing of basic concept in the context of consistent perception in implementation peace education for elementary schools children. Learning materials for students are emphasized in habit and implementation of cohabit harmoniously life ethic. The teaching model of peace behavior includes steps: (1) teachers' recommendation and drive for good behavior, (2) teachers' control and observation toward students' behavior, (3) class discussion about observation results in social studies education and or Pancasila and citizenship education. (4) continuing the implementation of good/peace behavior, (5) development good/peace behavior habit.   Abstrak: Penelitian dan pengembangan ini bertujuan mengembangkan model pembelajaran pembentukan perilaku damai dengan revitalisasi nilai kearifan lokal. Subyek penelitian di SD Propinsi Nusa Tenggara Barat. Hasil penelitian (1) modul untuk guru, dan (2) bahan pembelajaran untuk siswa. Modul untuk guru lebih ditekankan pada pengembangan konsep dasar dalam rangka penyamaan persepsi untuk menerapkan pendidikan perdamaian bagi anak-anak di SD. Bahan pembelajaran untuk siswa menekankan pada proses pembiasaan dan pelaksanaan etika hidup bersama secara harmonis di masyarakat. Model pembelajaran pembentukan prilaku damai meliputi tahapan (1) ajakan dan dorongan oleh guru berbuat baik, (2) kontrol dan pengamatan oleh guru terhadap perilaku siswa, (3) membahas dalam kelas hasil pengamatan dalam pelajaran IPS dan atau PKN, (4) melanjutkan menerapkan perilaku baik/damai, (5) terbentuk kebiasaan perilaku damai.